The Implication of the Thalamus in Speech Disturbance in a Boy with Rolandic Epilepsy - Kanemura, Hideaki; Sano, Fumikazu; Ohyama, Tetsuo; Sugita, Kanji; Aihara, Masao (Journal of Pediatric Epilepsy, 2017)
Transient oromotor deficits in children with rolandic epilepsy (RE) have been described in literature. It has been reported that thalamic aphasia can be caused by thalamic infarction or hemorrhage; however, it has never been reported that thalamic aphasia can be caused by epileptic disorders. Here, we describe a 6-year-old right-handed boy who showed transient oromotor deficits and speech disturbance with worsening of both epileptic seizure and paroxysmal discharges on electroencephalogram. He had paucity of spontaneous speech, feeble speech, arrest of speech, and anomia, but his repetition skills were intact. A single-photon emission computed tomography (SPECT) scan using technetium-99m hexamethyl propylene amine oxime (99mTc-HMPAO) to measure regional cerebral blood flow showed a reduction in flow in the left thalamus and ipsilateral frontotemporal areas, which appeared concurrently with the speech dysfunction. We suggest that speech disturbance such as thalamic aphasia, which is similar to the symptoms of Landau-Kleffner syndrome, may occur due to epileptic disorders such as RE. It may be possible to miss speech disturbance implicated in the thalamus in cases complicated by oromotor dysfunction. It is important that speech disturbance implicated in the thalamus is not overlooked in patients with RE showing an atypical course.
Keywords: rolandic epilepsy; thalamus; Landau-Kleffner syndrome; single-photon emission computed tomography